Pengembangan Buku tentang Perkembangan Peradaban Jembatan berbasis PjBL untuk Menumbuhkan Karakter Senang Belajar - Hayuka Nawang Pawestri; Gregorius Ari Nugrahanta (Universitas Cokroaminoto Palopo, 2024)
Currently, many issues regarding the love of learning character are still found. The low interest in learning among children is caused by a lack of motivation, due to the adaptation process during the transition from online learning to offline learning. The aim of this study is to develop a textbook on bridge civilization based on Project-Based Learning to foster a love of learning character. This textbook is the result of research using the ADDIE model through the R&D method. The study involved ten certified teachers from various regions for needs analysis and ten validators consisting of five certified teachers and five experts for expert judgment, as well as eight children for limited trials. The evaluation results from the validation of the book through the ADDIE stages yielded an average score of 3.89 on a scale of 1 – 4, indicating the textbook is in the 'very good' category with the recommendation 'no revision needed.' The bridge civilization textbook significantly impacts the love of learning character (p < 0.05) with an effect size in the large effect category (r = 0.95), equivalent to a 91% influence. The level of implementation effectiveness falls within the 'Moderate' effectiveness category (N-Gain Score 63.84%). Therefore, it can be concluded that the implementation of this bridge civilization textbook based on Project-Based Learning can foster the love of learning character in children.